Ultra light cellular structure—French approach - Perrier, H. (Geotextiles and geomembranes, 1997)
The increasing number of embarkments constructed in France using ultralight materials have produced in addition to expanded polystyrene new cellular materials designed for the same purpose with the special property of allowing water to rise inside the fill during flooding. These materials, Nidaplast in 1986 and Géolight in 1991, have been carefully studied at the Centre d'Expérimentation Routière (Road Research Centre), in Rouen, light-weight embankments made of cellular materials have been constructed at several sites (around 130000 m 3 have currently beenn used), and during the last few y Various ultra light cellular structures (ULCS) have already been used in road construction.